Preface - Zapf, Michael; Evers, Florian (Electronic Communications of the EASST, 2013)
This is the preface for Volume 56: Proceedings of the Combined workshop on Self-organizing, Adaptive, and Context-Sensitive Distributed Systems and Self-organized Communication in Disaster Scenarios (SACS/SoCoDiS 2013)